A review of the association between air pollutant exposure and allergic diseases in children - Lee, Jae Young; Lee, Seung-Bok; Bae, Gwi-Nam (TURKISH NATL COMMITTEE AIR POLLUTION RES & CONTROL-TUNCAP, 2014)
We reviewed the results of previous studies that investigated the association between allergic symptoms in children and exposure to the major air pollutants, here identified as nitrogen dioxide (NO2), ozone (O-3), particulate matter (PM2.5 and PM10), volatile organic compounds (VOCs), sulfur dioxide (SO2), soot, and carbon monoxide (CO), in terms of the odds ratios reported. We also reviewed a common procedure used in previous studies for building a whole study design based on application of an observational research method and various analysis models. Most previous studies reported odds ratios above unity and found a positive association between allergic symptoms and exposure to major air pollutants. When the strength of the associations between exposure to air pollutants and allergic disease in children were compared by normalization of the odds ratios, exposure to PM2.5 was found to have the strongest association, followed by NO2, while exposure to PM10 was found to have the weakest association.
Keywords: VOLATILE ORGANIC-COMPOUNDS; INDOOR NITROGEN-DIOXIDE; SUSPENDED PARTICULATE MATTER; CHRONIC RESPIRATORY SYMPTOMS; TAIWANESE SCHOOL-CHILDREN; CHILDHOOD ASTHMA; BRONCHITIC SYMPTOMS; HOSPITAL ADMISSIONS; ATOPIC-DERMATITIS; OZONE EXPOSURE